Electronic structure, optical dispersion and luminescence properties of terbium gallium garnet crystal. Issue 4 (6th January 2022) - Zhang, Haotian; Gao, Yuxi; Huang, Changbao; Chen, Yingying; Dou, Renqin; Zhang, Qingli
Abstract : Electronic structure, optical dispersion and luminescence properties of terbium gallium garnet (Tb3 Ga5 O12, TGG) were investigated. Abstract : Terbium gallium garnet (Tb3 Ga5 O12, TGG) is widely investigated due to its multifunctional applications. However, the electronic structure, optical dispersion properties, bandgap and luminescence mechanisms of the TGG crystal are still not reported. In this study, density functional theory (DFT) calculations were performed to investigate the electronic structure of TGG. The TGG single crystal was grown by the Czochralski method, and its dispersive refractive index, transmission spectrum and photoluminescence spectrum were measured. The first-principles calculation indicates that some of the 4f n configuration component of Tb 3+ was mixed into the conduction band, and some component of the 5d state was mixed into 4f state in the gap of TGG, which partially removed the parity forbidden rule, and resulted in the 5 D4 → 4 F J optical transition. The Wemple DiDomenico (WDD) model was employed to fit the measured refractive indices, which gave its dispersion energy and optical bandgap. The bandgap of TGG was determined as equal to 3.83 eV, 3.76 eV and 3.85 eV by the DFT model, WDD model and Tauc's plot, respectively.